Active training for amblyopia in adult rodents - Sale, Alessandro; Berardi, Nicoletta (Frontiers in Behavioral Neuroscience, 2015)
Amblyopia is the most diffused form of visual function impairment affecting one eye, with a prevalence of 1-5% in the total world population. Amblyopia is usually caused by an early functional imbalance between the two eyes, deriving from anisometropia, strabismus, or congenital cataract, leading to severe deficits in visual acuity, contrast sensitivity and stereopsis. While amblyopia can be efficiently treated in children, it becomes irreversible in adults, as result of a dramatic decline in visual cortex plasticity which occurs at the end of the critical period in the primary visual cortex. Notwithstanding this widely accepted dogma, recent evidence in animal models and in human patients have started to challenge this view, revealing a previously unsuspected possibility to enhance plasticity in the adult visual system and to achieve substantial visual function recovery. Among the new proposed intervention strategies, non invasive procedures based on environmental enrichment, physical exercise or visual perceptual learning appear particularly promising in terms of future applicability in the clinical setting. In this survey, we will review recent literature concerning the application of these behavioral intervention strategies to the treatment of amblyopia, with a focus on possible underlying molecular and cellular mechanisms.